Analisis Kelayakan Pendirian Usaha CV.Wisnu Motor di Jl.Leminggir Mojosari - Kusuma, Wisnu Wijaya; Singgih, Mochammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The feasibility analysis for establishing a CV. Wisnu Motor business on Jl. Leminggir Mojosari aims to determine the feasibility of a company. In an analysis of the feasibility of establishing a business, it can be carried out through several aspects, namely a monetary perspective, a special perspective, a market perspective and an advertising perspective using the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP) technique. ) and Profitability Index (PI). This analysis produces data that shows the NPV of the CV business establishment. Vishnu Motor for Rp. 1,974,607,419, with an IRR of 30.25%, then the PP for the business is 1 year 4 months 8 days, and the PI is 2.43. According to the existing analysis regarding feasibility here, it can be concluded that the CV. Wisnu Motor establishment business has fulfilled the feasibility of being established, because it has a positive NPV value, a higher IRR on funding costs, a relatively short PP, and a PI that shows greater than above.